Discussing global health security. Critical lessons from the 24th Ebola Virus Epidemic (Comillas Journal of International Relations, 2018)
This article proposes a critical reflection on the international political response given to the 24th Ebola epidemic that spread through the states of Guinea Conakry, Sierra Leone and Liberia (2014- 2016). We organize the article in three sections. Firstly, we locate this international response into the international medicalization history. Secondly, we use critical security studies to understand how the global health security policies deployed during the epidemic defended the interests of Western states over the needs of African societies. Thirdly, we propose a multidisciplinary vision to answer the previous criticism and to open new ways to overcome the Eurocentric global health security paradigm.
Keywords: ebola; Africa; health security